Analisis Tingkat Kebisingan Di Area Pasar Gede Solo - Vania Maharani Rizky Pratiwi; Sarwendah Dwi Juniati; Muhammad Reynaldy Putrayuda; Muchammad Sholiqin; Siti Rachmawati (DPPM Universitas Pelita Bangsa, 2022)
Noise is unwanted sound produced by a business or activity at a certain volume and frequency. Noise has an negative effect on quality of life, health and well-being. The market as a center for trade and services supported by the increasing number of vehicles used by the public is expected to cause uncontrollable noise. Measurement of noise levels in the market environment can be done to find out how much noise is generated from market activities and what kind of effect is generated. Therefore, this research was conducted which aims to determine the noise intensity measured by the calculation of the leq equation, to determine the effect of noise levels on community activities in the Pasar Gede Solo area, and to determine the effect of noise on humans or the whole environment in the Pasar Gede Solo area. The research was conducted on April to Mei 2022 at Pasar Gede Solo, Jl. Jend. Urip Sumoharjo, Sudiroprajan, Kecamatan Jebres, Surakarta City, Central Java. The method used in this research is descriptive quantitative method using primary data obtained by direct observation at the research location, distributing questionnaires, and conducting interviews with traders, workers, and buyers. In addition, secondary data obtained by literature study is also used. From the results of this study, it is known that the noise level at the front entrance has an average of 70.6 dB, the middle area is 62.9 dB, and the rear entrance is 65.1 dB. Among the three points, the front entrance has passed the predetermined threshold value. Noise levels that exceed the threshold value can cause hearing, communication, and physiological disturbances to traders, workers, and buyers in the Pasar Gede Solo area. Keywords: Noise Level, Pasar Gede Solo